History repeats itself: great challenges for weak governments - Portillo-Riascos, Luis Hernando (Universidad y Salud, 2020)
Introduction: COVID-19 represents an unprecedented phenomenon in recent human history. This new situation requires a strong official intervention to mitigate the socioeconomic impact caused to date. Objective: To assess the measures adopted by the Colombian government and oficial institutions of the Nariño Department (State) facing the social and economic challenges associated with COVID-19. Materials and methods: A documentary review based on government data, reports released by national and international research institutes, press communications and the Web of Science and Science Direct databases. Results: Information from fiscal administrative acts promulgated by different government entities to meet the obligations derived from COVID-19 during the March-May 2020 period was structured. Conclusions: Both the Colombian national government and local authorities from the Nariño Department have had to assume extraordinary expenditures to confront the costs associated with the COVID-19 pandemic. However, these measures seem insufficient and belated in the face of the magnitude of the effects caused by the pandemic.